The Influence of Tourism Facilities on Tourist Visits to Lake Tapala, Hatunuru Village, East Taniwel District, West Seram Regency - Lumapelemey, Indri; Papilaya, Josef; Rehatta, Geradin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
This study discusses the influence of tourism facilities on tourist visits to Lake Tapala, West Seram Regency. This study uses a quantitative descriptive approach with a population of all Lake Tapala and Hatunuru Village visitors. A sample of 35 respondents was selected using purposive sampling. Data collection methods include observation, questionnaires, interviews, and documentation. The dependent variable is Tourist Visits (Y), while the independent variable is Tourist Facilities (X), measured using a Likert scale. The analysis results show a significant relationship between tourist facilities and the number of tourist visits. The positive regression coefficient indicates that improving facilities will increase tourist visits to marketing theory, which states that adequate facilities increase tourist satisfaction. Investment and development of tourist facilities at Lake Chapala are expected to increase the destination's attractiveness and contribute to local economic growth and sustainable tourism development. Recommendations for local governments and destination managers are to continue to improve tourist facilities to support tourism growth. Promotion efforts are also needed through social media and information technology to increase the visibility and attractiveness of the destination.